2005
DOI: 10.1037/1528-3542.5.1.103
|View full text |Cite
|
Sign up to set email alerts
|

Enhanced Priming for Trauma-Related Material in Posttraumatic Stress Disorder.

Abstract: Intrusive reexperiencing in posttraumatic stress disorder (PTSD) has been linked to perceptual priming for trauma-related material. A prospective longitudinal study (N ϭ 69) investigated perceptual priming for trauma-related, general threat, and neutral words in assault survivors with and without PTSD, using a new version of the word-stem completion task. Survivors with PTSD showed enhanced priming for trauma-related words. Furthermore, priming for trauma-related words measured soon after the trauma was associ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
86
1
13

Year Published

2007
2007
2020
2020

Publication Types

Select...
7
3

Relationship

1
9

Authors

Journals

citations
Cited by 101 publications
(110 citation statements)
references
References 38 publications
10
86
1
13
Order By: Relevance
“…Several studies have found increased implicit and explicit emotional memory functions in patients with PTSD (17)(18)(19), but also the opposite has been reported (20). It is important to note that data on memory performance acquired in patients with PTSD are difficult to interpret, because changes in mood, motivation, attention, or arousal can indirectly affect memory performance in both directions.…”
Section: Discussionmentioning
confidence: 92%
“…Several studies have found increased implicit and explicit emotional memory functions in patients with PTSD (17)(18)(19), but also the opposite has been reported (20). It is important to note that data on memory performance acquired in patients with PTSD are difficult to interpret, because changes in mood, motivation, attention, or arousal can indirectly affect memory performance in both directions.…”
Section: Discussionmentioning
confidence: 92%
“…According to van der Kolk [170, 176], the suppression of hippocampal functioning and activation of the amygdala during horrific experiences underly the implicit, fragmented, and primarily sensory structure of traumatic memories. Traumatic memories certainly have a powerful implicit (nondeclarative) component, and PTSD patients commonly have amnesia, or “memory gaps,” for events that occurred during their trauma (van der Kolk et al [194]; van der Kolk [176]; van der Kolk [170]; Joseph [171]; Yovell et al [195]; Michael et al [196]; Ehlers et al [197]). However, traumatized people commonly provide explicit (declarative) descriptions of the event(s) that precipitated their PTSD symptoms.…”
Section: Cracks In the Edifice Of The Hypothesis That Strong Emotimentioning
confidence: 99%
“…La premiere est que I'augmentation de l'attention lors de l'encodage favorise l'acces a la rememoration consciente du souvenir (Ochsner, 2000), Or, cbez les participants souffrant de TSPT les informadons negatives subissent un traitement plus intense dans la mesure ou elles constituent des elements externes susceptibles de reveiller les souvenirs repetes et intrusifs de l'evenement traumadque (Williams et al,, 1996), La seconde concerne le fait que dans le TSPT, I'histoire traumatique qui est a I'origine du trouble rend les informations negatives plus aisement assimilables a des souvenirs personnels que d'autres types d'informations (McNally, 1995), Or, il a ete montre que le fait de pouvoir relier les informations a memoriser a des elements de son histoire personnelle (reference a soi) les rend plus distinctes et plus aptes a declencher des details episodiques reladfs a leur contexte d'apprendssage (Eujita & Horiuchi, 2004). Ainsi, le biais de recuperation pour les informations a connotation negative observe chez les participants souffrant de TSPT pourrait refieter le mecanisme par lequel les stimuli anxiogenes activent les souvenirs en lien avec le traumadsme (Tapia et al,, soumis), Einalement, ces donnees suggerent que le biais de memoire largement observe dans les etudes qui ont porte sur la memoire explicite n'est en fait avere que pour la composante autonoetique du processus de recuperation, Aussi, l'avantage mnesique apporte par les informations a connotation traumatique ne se traduit pas uniquement par une augmentation du nombre d'informations rappelees mais permet egalement d'elever la qualite des informations recuperees, Le fait que cet acces a la conscience autonoedque soit anormalement facilite dans le TSPT pourrait refieter I'hypersensibiiite de ces patients vis-a-vis des stimuli potentiellement menagants, Biais de memoire dans la memoire implicite Contrairement a la memoire explicite, les travaux portant sur les performances en memoire implicite dans le TSPT n'ont pas reveie I'existence de deficit pour ce type de memoire (Golier, Yehuda, Lupien, Harvey, Grossman & Elkin, 2002), Cependant, avec un materiel connote, des effets sous la forme de biais de memoire ont ete observes cbez les pardcipants souffrant de TSPT, Michael, Ehlers et Halligan (2005) ont utilise un paradigme de completement de trigrammes chez 69 participants ayant subi une agression (physiques, avec une arme ou sexuelles) en faisant varier la connotation emotionnelle des mots a encoder (mots lies a l'agression, mots mena^ants, mots neutres). Les resultats ont revele que parmi ces 69 participants, les 26 qui ont developpe un TSPT montralent un effet d'amorgage plus important pour les mots specifiquement lies a l'agression compares aux autres participants traumatises sans TSPT.…”
Section: Biais De Memoire Dans La Memoire Expliciteunclassified